PENGARUH KARAKTERISTIK KERJA, KOMPENSASI, DAN KEPUASAN KERJA TERHADAP KOMITMEN GURU EKONOMI PADA SEKOLAH MENENGAH ATAS (SMA) NEGERI PROVINSI BALI - Sudiarditha, I Ketut R. (Parameter, 2017)
In particular the aims of this research are: (1) to knew the direct effect of job characteristics toward job satisfaction of teachers. (2) to knew the direct effect on job satisfaction of teachers' compensation. (3) to knew the direct effect of job characteristics on teacher commitment. (4) to knew the direct effect of the components of teacher compensation. (5) to knew the direct effect of job satisfaction on the teachers commitment.The research was conducted at the High School (SMA) State of Bali Province which spread across nine counties and cities. The method used was survey method with causal techniques. The population in this study were all teachers who have passed the certification economics profession at High School (SMA) State of Bali province. The number of samples in the analysis suggested by Solimun Structural Equation Modeling (SEM) of 400. The findings of this study indicate that: (1) there was a direct effect of the positive characteristics of the work on job satisfaction of teachers; means that the characteristics of the corresponding work will increase the job satisfaction of a good teacher. (2) there was a direct influence on job satisfaction of teachers' compensation; synonymous with high compensation will increase the job satisfaction of good teachers. (3) there was a direct positive effect on the commitment of teachers' job characteristics; means that the characteristics of the corresponding work will increase the commitment of a good teacher. (4) there was a direct positive effect on the commitment of teachers' compensation; synonymous with high compensation will increase the commitment of a good teacher. (5) there was a direct positive effect on the commitment of teachers' job satisfaction; synonymous with high job satisfaction will increase the commitment of a good teacher. Abstrak Secara khusus tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui pengaruh langsung karakteristik kerja terhadap kepuasan kerja guru; kompensasi terhadap kepuasan kerja guru; karakteristik kerja terhadap komitmen guru; kompensasi terhadap komponen guru; dan kepuasan kerja terhadap komitmen guru. Penelitian dilakukan di Sekolah Menengah Atas (SMA) Negeri Provinsi Bali yang tersebar di sembilan kabupaten dan kota. Metode yang digunakan adalah metode survei dengan teknik kausal. Populasi dalam penelitian ini adalah seluruh guru ekonomi yang telah lulus sertifikasi profesi pada Sekolah Menengah Atas (SMA) Negeri Provinsi Bali. Temuan hasil penelitian ini menunjukkan bahwa terdapat pengaruh langsung positif karakteristik kerja terhadap kepuasan kerja guru; kompensasi terhadap kepuasan kerja guru; karakteristik kerja terhadap komitmen guru; kompensasi terhadap komitmen guru; dan kepuasan kerja terhadap komitmen guru; artinya dengan kepuasan kerja yang tinggi akan meningkatkan komitmen guru yang baik.